Which are the consequences of vectoring technology, broadcast services and business services on NGA recommendation implementation - Alain Maton (International Telecommunications Society (ITS), 2012)
Competition by FTTH infrastructure is not an universal solution to solve competition on broadband markets. In addition the border between broadband products and leased lines products becomes less clear Competition of legacy copper networks Eurodocsys 3 obliges to increase VDSL performance. Unfortunately, the present state of the proposed technology - the vectoring - is incompatible with subloop unbundling. Without subloop unbundling, there is no possibility for alternative operator to provide broadcast TV services and triple play with the risk to be out of market. Multicast is a huge investment for SMP operator and a huge operational cost for small and medium alternative operator, so the sharing of the IPTV platform can be a win-win alternative but not in the scope of the related bitstream market. Challenging leased lines in NGN environment where bitstream should be the main tool needs also an adapted assessment of these markets.
Keywords: 330; electronic communications; access regulation; market analysis; unbundling; vectoring; bitstream; broadcast; leased lines